Infected “Mycotic” Aneurysm of the Common Carotid Artery—A Differential Diagnosis to Tumor of the Neck - Eriksen, Patrick R. G.; Hvilsom, Gitte B.; Homøe, Preben (Frontiers in Surgery, 2018)
Introduction: Infected “mycotic” Aneurysm (IA) of the extracranial carotid artery is a rare condition that can be fatal if mistaken for other pathology. An 83-year-old man presented with a mass on the neck initially suspected malignant. Weeks later it grew rapidly and was found to be an IA, thus requiring acute surgery. Via this case report, we discuss diagnostics and approach when diagnosing masses in relation to vessels of the neck not readily explained. Case Report: After diagnostic imaging and clinical assessment an unknown primary tumor of the neck was suspected. Fine needle aspiration was inconclusive. The patient did not present with any signs of infection or neurological symptoms—only discomfort and pain. Approximately two weeks later, the mass grew and the patient became dysphagic, febrile, and confused. Computed tomography angiography revealed an IA of the right common carotid artery. The patient underwent acute surgery consisting of ligation of the internal and external carotid arteries and resection of the internal jugular vein. The pathogen found was E. coli, supposedly from the bladder after surgical intervention due to polyposis. Conclusion: IA is a very rare entity and can have many etiologies. Since it can be fatal, it is necessary to keep IA in mind when diagnosing masses in relation to vessels of the neck. As shown in this case of a E. coli-induced IA, patients can present with atypical symptoms, on diagnostic imaging it can be mistaken for other pathology, and pathogenesis can be unclear.